Smoking Intensity Among Male Factory Workers in Kunming, China. (March 2015) - Cheng, Kai-Wen; Tsoh, Janice Y.; Cui, Wenlong; Li, Xiaoliang; Kohrman, Matthew
Introduction . This study investigated the intensity of cigarette consumption and its correlates in China among urban male factory workers, a cohort especially vulnerable to tobacco exposure, one that appears to have benefitted little from recent public health efforts to reduce smoking rates. Methods . Data were collected from men working in factories of Kunming city, Yunnan, China, who are current daily smokers (N = 490). A multinomial logistic regression was conducted to examine the factors in association with smoking intensity in light, moderate, and heavy levels. Results . Light smoking correlated with social smoking, smoking the first cigarette later in the day, self-reported health condition, and quit intention. Heavy smoking was associated with purchase of lower priced cigarettes, difficulty refraining from smoking, and prehypertensive blood pressure. Conclusion . Even in regions where smoking is highly prevalent, even among cohorts who smoke heavily, variation exists in how cigarettes are consumed. Analyses of this consumption, with special consideration given to smoking intensity and its correlates, can help guide tobacco-control strategists in developing more effective interventions.